The Legal Studies Regarding Professional Zakat in Islam and for the Benefit of the Ummah - Tobroni, Ahmad (Law Development Journal, 2022)
This study aims to find out how the concept and application of professional Zakat in Islam are then harmonized with the concept of state taxation. This research is a qualitative research with an interpretive approach to the law that applies both in Islamic law and national tax administration law. The main sources in this study are the Al-Qur'an and Sunnah as well as laws and regulations regarding the Zakat system and taxation of the Indonesian State, then analyzed in depth to draw conclusions. The results shown that professional Zakat is special Zakat that is issued from the results of what is obtained from work and profession. For example, work that generates good money is work that is done alone without depending on other people, thanks to the dexterity of the hands or brain (professional).